Morphology and mechanical properties of poly(β-hydroxybutyrate)/poly(ε-caprolactone) blends controlled with cellulosic particles. (15th October 2017) - Chen, Jianxiang; Wang, Yuankun; Yin, Zeren; Tam, Kam C.; Wu, Defeng
Highlights: MCC is dispersed independently of two polymer phases in PHB/PCL blends. EC are located in PCL phase and on the phase interface of PHB/PCL blends. Those selective localizations affect final morphology and properties of blends. Providing a new way to moderate properties of blends with cellulose particles. Abstract: The rigid microcrystalline cellulose (MCC) particles and semi-rigid ethyl cellulose (EC) were used to control phase morphology and mechanical properties of immiscible poly(β-hydroxybutyrate) (PHB)/poly(ε-caprolactone) (PCL) blends. The interfacial properties were evaluated by the fiber retraction and contact angle methods MCC is incompatible with PHB and PCL, and dispersed independently in the two polymer phases in their blends. However, EC is more compatible with the two polymers, with a higher affinity for PCL. And EC prefers locating in PCL domains and at the phase interface. Selective localization of MCC and EC affects the mechanical properties and phase structure of PHB/PCL blends strongly. For the co-continuous samples, the presence of MCC and EC improves both the tensile and impact strengths. For the 'sea-island' ones, however, the changes of strengths depends strongly on the phase adhesion. This work will help focus efforts on moderating structure and properties of immiscible polymer blends using cellulose particles.